Pengaruh Physical Evidence Terhadap Keputusan Pembelian Konsumen Di Happy Cow Palasari Bandung (Survey Pada Konsumen Di Happy Cow Palasari Bandung) - Sabrilia, Tinka; Andari, Rini; Abdullah, Taufik (Universitas Pendidikan Indonesia, 2016)
Tourism has become one of the largest industries in the world, and are themainstay in generating foreign exchange in many countries, including Indonesia with a very vast natural wealth. In a world traveler tourism industry can not be separated from tourism accommodation ranging from lodging services, transport and restaurants. Which at this present moment tourism is much discussed is culinary, talk about the culinary is a city rich in culinary. One of the restaurants in the city of Bandung, Happy Cow Steak Palasari Bandung is located in Jalan Palasari No. 30, Bandung. With the passage of time and an increasingly tight competition in restaurant sales decreased. It is seen from the sales data Happy Cow Steak Palasari Bandung has decreased the number of consumers in 2015 amounted to 15.3%. One of the strategies used to increase the return of consumer purchasing decisions, namely physical evidence. Increased physical evidence aimed to withdraw the interest of consumers to make purchases at the Happy Cow Steak Palasari Bandung.The object in this research is that consumers in Happy Cow Steak PalasariBandung. The independent variable in this study is physical evidence and thedependent variable is buying decision. This study uses descriptive and verification method, with explanatory survey method. The number of samples in this study of 100 respondents. Data analysis technique used is the technique of multiple regression analysis with the program.Based on the results of studies found that physical evidence has a positiveinfluence on purchasing decisions with that middle relationship categories.